PRELIMINARY RESULTS FROM THE SYNERGIC TRIAL: A MULTIMODAL INTERVENTION FOR MILD COGNITIVE IMPAIRMENT. (11th November 2018) - Montero Odasso, M; Almeida, Q; Camicioli, R; Li, K; Liu-Ambrose, T; Middleton, L; Bherer, L
Abstract: Mild Cognitive Impairment (MCI) is a prevalent pre-dementia state. Emerging evidence supports that physical exercise and computerized cognitive training can independently improve cognitive outcomes. Recently, vitamin D deficiency has been associated with increased risk of progression to dementia. To date, a multimodal intervention based on physical exercises, combined with computerized cognitive training and vitamin D supplementation has not yet been tested in MCI. The SYNERGIC Trial (SYNchronizing Exercises, Remedies in Gait and Cognition) is a multisite clinical-trial aimed to improve cognition and delay progression from MCI to dementia, using the aforementioned multimodal intervention. 200 participants with MCI are being assigned to active or sham interventions. Active interventions (3 days/week) include combined aerobic and progressive resistance training exercise, progressive cognitive training, and vitamin D supplementation (4000 IU/daily) for 6 months. Control interventions consist of balance and toning exercises, control cognitive training, and placebo vitamin D. Primary outcome is improvement in ADAS-Cog 13 (range 0–84; lower scores indicate better cognitive function). ANCOVA adjusting for baseline values was the primary analysis. ClinicalTrials.gov Identifier: NCT02808676. Preliminary results show that combining exercise and cognitive training showed the best improvements on ADAS-Cog 13 after 6 months, followed by combined exercise (combined exercise and cognitive training: 11.67 ± 4.58; combined exercise: 15.29 ± 6.64; balance and toning: 20.77 ± 9.67; p= 0.010). The control group did not improve ADAS-Cog 13 scores. Our preliminary results show that a multimodal intervention with physical and cognitive training is feasible and have a positive effect in improving cognition in MCI.